Metropolitan Detroit's Network “...informed by magic numbers.” - Sullivan, Howard A. (1968)
Wayne State University Library's serials automation project is evolutionary in concept, with its first completed stage designed to give information on titles and holdings. Its master tape includes, in addition to Wayne State University holdings, data for more than twenty biomedical libraries in the area, and print options are available that will produce a full union list or individual lists singly or in any combination.